Peningkatan Literasi Islami sebagai Upaya Pembinaan Karakter Masyarakat di Kelurahan Timbang Langkat - Dahlia Summayah Sitorus (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study was motivated by the low level of Islamic literacy among the people of Timbang Langkat Village, which has affected the development of character based on Islamic values. The purpose of this research is to enhance Islamic literacy as an effort to strengthen community character through a two-week community service activity using a participatory and collaborative approach. This study employed a descriptive qualitative method with an action research model. Data were collected through observation, interviews, and questionnaires involving 30 participants, including community leaders, mosque youth, and local residents. The findings revealed a significant improvement in the community’s understanding of Islamic literacy, increasing from 40% of participants in the “good” category before the activity to 83% afterward. In addition to improved understanding, there was also a noticeable shift in social behavior reflecting Islamic values such as honesty, discipline, responsibility, and social awareness. The implication of this study suggests that Islamic literacy plays an essential role in shaping the community’s religious character and can serve as an effective strategy for moral and spiritual development. This Islamic literacy-based community service program is expected to be developed sustainably in other regions, adapted to local social and cultural contexts.